Food neophobia amongst young Malaysians - understanding young Malaysian perceptions of novel foods concerning individual demographic backgrounds / Khairul Azfar Adzahar … [et al.] - Adzahar, Khairul Azfar; Jamaludin, Mohd Fazil; Saharan, Mohd Shafiz; Abdul Ghani, Rosmaiza; M Antara, Purnomo (2023)
This study aims to examine the demographic background effect on food neophobia among young Malaysians. Quantitative tools were employed in the study through a questionnaire survey. Nonprobability convenience sampling was implemented, and the questionnaire was distributed to 200 respondents to represent the total population. All collected data was then analyzed using SPSS. The acceptance and adoption of certain foods by young Malaysians were influenced by various demographic factors, especially age. As the age increases, the scores are lower. Besides, young Malaysians' who are female, live in a more urbanized area and hold a tertiary education level, may play a role in reducing their food neophobia scores. The study suggests that understanding the various demographic factors that influence young Malaysians' food choices can help marketers develop competitive strategies to promote new food products. This study examines food neophobia based on the demographic background among young Malaysians.